Le jardin alpino-japonais Les Roches Fleuries, un proto-manifeste in situ du mouvement de réforme belge Le Nouveau Jardin Pittoresque ? - Ursula Wieser Benedetti (Projets de Paysage)
The Alpine-Japanese garden of Les Roches Fleuries, located in Genval in the Walloon Brabant region, is one of the most astonishing Belgian works of landscape architecture of the first half of the 20th century. Created between 1910 and 1932 by the geologist, palaeontologist and botanist Ernest Van den Broeck (1851-1932), a leading figure in the natural sciences at the time, it remains largely unknown today. Apart from a few articles from the period and a study published in a local historical journal, this garden, which was a botanical and artistic reference in Belgium and beyond until the 1930s, gradually fell into oblivion. This article sheds light on the genesis of the work, its close ties with the Belgian movement of the Nouveau Jardin Pittoresque (The New Picturesque Garden), and the extraordinary convergence of influences of the English Wild Garden, the Alpine Garden, the Belgian Scientific Garden and the Japanese Garden that inspired its creator. The "Alpine-Japanese" concept, forged in a dialogue with the Swiss botanist Henry Correvon, resulted in a garden the charm of which is still striking despite the disappearance of many of its elements over the decades. Alpine flora, East Asian flora, geology and garden design come together in a way that is both poetic and scientific. These ingredients are perfectly aligned with the principles of the Nouveau Jardin Pittoresque, a movement founded three years after the creation of the garden at Genval. The question we raise, is whether this garden was the in situ proto-manifesto of the Nouveau Jardin Pittoresque?